2017
DOI: 10.1177/0309364616661254
|View full text |Cite
|
Sign up to set email alerts
|

Effects of foot orthoses with medial arch support and lateral wedge on knee adduction moment in patients with medial knee osteoarthritis

Abstract: Our study suggests that customized foot orthoses with a medial arch support may only be suitable for the management of medial knee osteoarthritis when a lateral wedge is included. Clinical relevance Our data suggest that customized foot orthoses with medial arch support and a lateral wedge reduce knee loading in patients with medial knee osteoarthritis (KOA). We also found evidence that medial arch support may increase knee loading, which could potentially be detrimental in KOA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 31 publications
0
37
0
1
Order By: Relevance
“…While some studies have shown reductions in the KAM when using a combined lateral wedge/medial arch support 24,25 , it appears that the reduction in KAM is largely driven by the lateral wedge orthotic 26,27 . In fact, findings suggest that the KAM is increased when a medial arch support is used in isolation 25,28,29 . However, recent additions to the market also include shoes with flat, thin, flexible soles which minimize interference with natural foot motion during walking.…”
mentioning
confidence: 98%
“…While some studies have shown reductions in the KAM when using a combined lateral wedge/medial arch support 24,25 , it appears that the reduction in KAM is largely driven by the lateral wedge orthotic 26,27 . In fact, findings suggest that the KAM is increased when a medial arch support is used in isolation 25,28,29 . However, recent additions to the market also include shoes with flat, thin, flexible soles which minimize interference with natural foot motion during walking.…”
mentioning
confidence: 98%
“…While walking, the foot and knee are biomechanically linked within a closed kinetic chain, and foot position and motion may influence the knee load . In fact, interventions using foot orthoses that aim to reduce knee loading and knee pain have been reported, and more are emerging …”
mentioning
confidence: 99%
“…Mean±SD of external knee adduction moment at early, mid, and late stance in 3 conditions: without insole, lateral wedge insole, and lateral wedge insole and a subtalar strap (n =17). 5 support ended to a protracted controversy (7,13,14,31). The possible explanations could be related to the variation among the sample of the studies or the interventions used in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to the findings of a randomized controlled trial (34), using a subtalar strap with LWI was not superior to using a subtalar strap with neutral insole on pain and physical function in KOA (34). One reason may be the arch support used in our insoles, as arch support tends to provide a COP medial shift and counteracts the lateral shift of the COP made by the wedge (31). However, customized arch support in LWI can improve pain, physical function, and foot function after 2 months (13) and EKAM in patients with KOA (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation